Firms' export decisions: Selection versus trial-and-error - Mohammad Movahedi; Kiumars Shahbazi; Ahmed Haidara Ould Abdessalam (Kiel Institute for the World Economy (IfW), 2019)
In this paper, an original and simple theoretical model is developed to better integrate various dimensions of the firms' decision to export. The model sheds light on the affirmations of the founding models of the "new theory of international trade", in particular the role of productivity and sunk costs of exporting in the firms' export decisions. It can also explain stylized facts that seem difficult to reconcile with the implications of the founding models: 1) flows of export market entry and exit are substantial; 2) entry into export markets would be rather gradual in the sense that firms start exporting small quantities and, if they survive, quickly expand their exports.
Keywords: F10; 330; firm heterogeneity; self-selection; sequential exporting